Cry wolf - Wadlow, Jeff.; Morris, Julian, 1983-; Booth, Lindy; Padalecki, Jared, 1982-; Bon Jovi, Jon.; McCoy, Sandra; Tirone, Romeo; Wandmacher, Michael; Universal Pictures (Firm) (Universal City, CA : Universal Pictures, 2005)
When a young woman is found brutally murdered, a group of local high school students decide to further scare their classmates by spreading online rumors that a serial killer called "The Wolf" is on the loose. By describing the next victims, the students' want to see how many people they can convince-- and if anyone will discover the lie. Unfortunately, when the described victims actually do start turning up dead, suddenly no one knows where the lies end and the truth begins.
Title from container.
Bonus features: The Tower of Babble: the award-winning short film that led filmmakers to Cry Wolf; deleted and alternate scenes; enter the sinister set: a tour with actor Julian Morris; Manual Labor: the short film that helped the filmmakers win the Chrysler Million Dollar Film Festival; wolves, sheep and shepherds: casting the roles; commentary by the filmmakers.
Director of photography, Romeo Tirone ; art director, Julie Smith ; editor, Seth Gordon ; music by, Michael Wandmacher ; costume designer, Alysia Raycraft ; production designer, Martina Buckley.
Julian Morris, Lindy Booth, Jared Padalecki, Jon Bon Jovi, Sandra McCoy, Kristy Wu.
Not rated; [for violence, terror, disturbing images, language, sexuality and a brief drug reference.]
DVD, region 1, anamorphic widescreen (2.35:1) presentation; Dolby Digital 5.1 surround, single sided, dual layer.
Keywords: Serial murders -- Drama; High school students -- United States -- Drama; Online chat groups -- Drama; Feature films; Thrillers (Motion pictures)